Ground Penetrating Radar for inspecting the core and base of coastal sand dunes - Alexopoulos, J.; Giannopoulos, I; Mitsika, G.; Gkosios, V; Konsolaki, A.; Vassilakis, E; Poulos, S. (2nd International Conference International Scientific Conference on Design and Management of Harbor Coastal and Offshore Works, 2023)
Coastal erosion induced either by a natural process and/or human intervention has been the subject of extensive investigations due to their negative socio-economic impact. ILIDA-KIT is an innovative and multi-parametric decision-making tool for successful management of coastal erosion and the impacts of storms. Thus, within the framework of the ILIDA-KIT tool, beach zone sectors of the west and south coast of Peloponnesus (Greece) (i.e. Helonitis Gulf, Kyparissiakos Gulf and Messiniakos Gulf) have been investigated with geophysical means, aiming to the quantification of the sediment budget that is essential for the confrontation of the phenomenon. The geophysical research aims to identify the thickness and the characteristics of the uppermost lithostarigraphic substratum of the selected beach zone sectors, whose common characteristic is the presence of dunes at the backshore zone. Apart of the other geophysical techniques (e.g. electrical resistivity tomography (ERT), transient electromagnetic soundings (TEM), vertical electrical soundings (VES)) that have been applied, the present contribution provides the preliminary results concerning the application of the ground penetrating radar (GPR) technique. The GPR electromagnetic method was implemented to profiles normal to the shoreline contributing to (a) the quantification of the erodible part of the beach zone and (b) the determination of the base of the sand dunes.